The Influence Of Tourism Product, Service Quality, And Authenticity On Revisit Intention Moderated By Cultural Spirituality In Tana Toa Village - fairuz hisana; Titien Damayanti; Lukia Zuraida (LP2M IAIN Palopo, 2025)
This study analyzes the influence of tourism products, service quality, and authenticity on domestic tourists’ revisit intention in Tana Toa Tourism Village, Bulukumba, South Sulawesi, with spirituality as a moderating variable. Tana Toa represents the Kajang indigenous community that upholds the kamase-masea philosophy and Pasang ri Kajang customary law, making it a spiritually unique destination rooted in local wisdom. Using a mixed-methods sequential explanatory design, quantitative data were obtained from 295 domestic tourists and analyzed through PLS-SEM, while qualitative insights were drawn from in-depth interviews with key informants. Findings reveal that tourism products, service quality, and authenticity significantly affect revisit intention. Spirituality moderates the relationship between authenticity and revisit intention, but not between tourism products or service quality and revisit intention. The study’s novelty lies in integrating indigenous spirituality as a moderating variable in cultural tourism research. Practically, the findings emphasize the importance of cultural–spiritual narratives as unique selling propositions that strengthen Tana Toa’s tourism sustainability.